Workplace Bullying: Implications for Adult Educators - Kathy M. Bonnar; Judy L. Skorek (Adult Education Research Conference, 2014)
Workplace bullying is when one person or a group in a workplace single out another person for unreasonable, embarrassing, and/or intimidating treatment. According to the Workplace Bullying Institute, up to a third of workers may be targets of bullying. Education and awareness are vital to protect all employees.